The critical friend – a way to develop as a tutor in problem-based learning groups - Sjögren, Elaine; Kärner Köhler, Anita (Högre utbildning, 2021)
Tutors in problem-based learning (PBL) need to reflect on their role, to prevent stagnation. We aimed to explore the learning experiences of tutors gained by being and having a critical friend in a PBL group. Eight teachers, from several professional programs at the Faculty of Medicine of a Swedish university, participated in a cross-program activity involving the being and having a critical friend to improve their skills as PBL group tutors. They were individually interviewed, and the transcriptions were subjected to conventional qualitative content analysis. The results revealed that a critical friend from another discipline can be useful and that experiences from both roles, to be and to have a critical friend, is necessary for reflection and learning, and thus optimal results. We conclude that support from the organisation, knowledge sharing, and communication are required to enable a systematic use of critical friends to be implemented with credibility.